ICT IN EDUCATION AS THE APPLIANCE OF THE DEVELOPMENT OF SPATIAL IMAGINATION OF LEARNERS - TOMKOVA, Viera (Journal of Technology and Information Education, 2015)
The report is addicted to the different means of learner's education with the support of IKT that develops their ability to read consciously, their spatial sensitivity, their ability of manipulation with objects in space and their ability to make their own graphical views of the sensed objects. The paper presents the research team results that have been achieved in the process of meeting goals of the KEGA project No. 035UKF-4/2012. The project concentrates on the development of the spatial imagination development of the lower secondary level learners. The main objective of the project was to design the methodology of technical education focused on the spacial imagination development and related graphic skills.
Keywords: education; spatial imagination; educational ICT